Fatores associados às concentrações séricas de fármacos utilizados no tratamento da tuberculose - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
Introduction: Tuberculosis (TB) is an infectious disease of high prevalence in Brazil. Thus, drug treatment used in the country is standardized by the TB treatment Basic Scheme and consists of rifampicin, isoniazid, pyrazinamide and ethambutol. The occurrence of low therapeutic levels of these drugs is reported in several people and many factors may contribute to this outcome. Therefore, this study aimed to determine the serum concentrations of antituberculosis drugs, and relating sociodemographic and laboratory variables with the levels obtained in samples from patients treated at a referral center in Manaus. Materials and Methods: This was an analyticalobservational cross-sectional study. The study population consisted of patients under treatment for TB treated at a referral center in the city of Manaus. The variables were compared between patients with low and normal serum using the chi-square test for categorical variables and Student's t test for continuous variables. For all the tests performed in this study, the significance level was 0.05. Results: Of 222 patients, 40.9% of patients had reduced serum levels for one of the tested drugs, and the prevalence of low more significant therapeutic levels were to isoniazid (60.8%) and rifampin (58.6%). Singles was found association with low serum concentrations of Isoniazid (p = 0.044), people with high school/graduate education (p = 0.028) and alcoholics (p = 0.038). Furthermore, in the case of Rifampicin, was association of people with a high school/graduate and lower therapeutic drug levels (p = 0.063). ANOVA analysis was performed and there was no association of the NAT2 genotypes and the serum concentrations with statistical significance (p <0.05). Conclusion: The presence of low concentrations of first-line drugs used to treat TB was found in a significant proportion of the population under study. Additional studies should be conducted to assess the impact of pharmacogenetics and adherence to treatment in these results, as well as to investigate the influence of low concentrations in treatment outcome.
Keywords: Níveis terapêuticos; Fármacos antituberculose; Monitorização terapêutica de fármacos; Farmacogenética; CIÊNCIAS DA SAÚDE: FARMÁCIA